Deep Breathing Relaxation To Overcome Back Pain In Pregnant Women - Komariah, Nurul; Wahyuni, Sari; Noviyanti, Lily; Dahliana, Dahliana; Virgian, Kharisma; Noviyanti, Asri; Ismalayani, Ismalayani (CV. AFDIFAL MAJU BERKAH, 2026)
Lower back pain during pregnancy occurs due to changes in the body's center of gravity, pelvic joint relaxation, and increased lumbar lordosis caused by weight gain and musculoskeletal adaptation as pregnancy progresses. Non-pharmacological approaches, such as deep breathing relaxation techniques, have been used in antenatal care to help pregnant women reduce pain and anxiety intensity without the side effects of medication. This Community Service activity was carried out on 20 pregnant women in the third trimester in the Sukajadi Health Center Area , Talang Kelapa District, Banyuasin Regency. The activity was carried out at the Sukajadi Health Center The activity was carried out in September-November 2021. The Community Service Activity aims to apply knowledge and technology so that the community can enjoy its results and feel the benefits. In the implementation of the Pengabmas activity, the service provider strives to make it as effective as possible so that it does not make pregnant women feel tired from the activity. The mother seemed enthusiastic in participating in the service activities, actively asking questions related to complaints during pregnancy. The mothers pain is reduced.